KERANGKA HUKUM PENGEMBANGAN USAHA BUMDES MELALUI ANAK PERUSAHAAN BUMN PTMITRA BUMDES NUSANTARA (STUDI DI BUMDES AMARTA) - Putri Raodah; Rahmadani Rahmadani (LPPM Institut Pendidikan Nusantara Global, 2023)
PT MBN is committed as an aggregator, off-taker, and executor of operational supervision for BUMDes in Indonesia. BUMDes business development by PT MBN is carried out indirectly through subsidiaries established by BUMDes and PT MBN. One of these subsidiaries is PT MD Sleman Sembada which is a jointly controlled entity and an object of control company. PT MBN gives reverse dividend rights and does not match the number of shares to BUMDes. There must be a meeting point between BUMDes goals as specified in Article 3 of Government Regulation Number 11 of 2021 concerning Village Owned Enterprises and the vision and mission of PT MBN. PT MD Sleman Sembada is placed as a controlled company because all decision making on the management of the company is under the full control of PT MBN as the majority shareholder. Nevertheless, the legal construction of limited liability and the legal independence of PT MD Sleman Sembada must also be considered in efforts to develop a just BUMDes business through PT DM Sleman Sembada.